Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa Di Sma Negeri 5 Kota Serang - Kurniawan, Satria Dimas; Putra, Arif Permana; Maryuni, Yuni (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the effect of the problem based learning model on students critical thinking skills of class XI students at SMA Negeri 5 Serang City. This research was conducted from May 2024 to October 2024. The research method used was quasi-experiment. The sampling technique in this study used a type of non-probability sampling with purposive sampling technique. The research sample totalled 43 students in class XI-S1 as the experimental group and 44 students in class XI-S2 as the control group. The instrument used in this study was a 10-item description test. Hypothesis testing was carried out using a two-party t-test with the polled variant formula obtained the value of t_hitung (10.6) ≥ t_table (1.99). with α = 0.05 so that HO is rejected and H1 is accepted. This shows that there is an effect of problem based learning model on critical thinking skills of class XI students at SMAN 5 Serang City on the material of Japanese Occupation in Indonesia. The problem-based learning model can be used as a recommendation for learning models to implement history learning and train students‘ critical thinking skills, this is because the problem-based learning model can construct historical knowledge about past problems and focuses on how students think in solving problems so that it can train students’ critical thinking skills. However, the problem-based learning model also has a disadvantage in that it requires more time to implement the stages of the problem-based learning model.